Implementasi Penataan Ruang Kelas di MTs Aulia Cendekia Palembang - Ibrahim; Hikmatul Hasanah; Ahmad Zainuri (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
Classroom arrangement is an important part of supporting the importance of education. Sometimes the arrangement of classrooms is not paid attention to, so that learning is not optimal, with this research, it aims to make educators aware of the importance of good classroom arrangement, in order to achieve the goals of an education. This research uses descriptive qualitative research methods or types, meaning to explain, describe or describe things in improving the learning achievement of eighth grade students of MTs Aulia Cendekia Palembang. Then the techniques used to collect research data are observation, interviews and documentation. This technique must be used during field reseach, in order to obtain the necessary data. Furthermore, after the data has been collected using these techniques, the next step is data analysis techniques, with data reduction, data presentation and drawing conclusions. The implementation of claasroom arrangement plays a major role in helping to create a learning process that is in accordance with the learning objectives. The arrangement of the classroom includes arrangement of student seating according to the physical condition of the student, arrangement of learning tools that are stored and used properly, installation of student work which includes forms of creativity and innovation of students, as weel as adequate lighting arrangements. Adequate in the importance of structuring the classroom. The results of this study are expected to be able to provide understanding to prospective teachers and become an evaluation for teachers that the implementation of classroom arrangement is important.